A mineiridade no modernismo: Aires da Mata Machado e o registro dos vissungos - Giovannini Junior, Oswaldo (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
Aires da Mata Machado Filho was an important writer and researcher miner of the twentieth century. Recorded a dialect spoken by descendants of slaves in São João da Chapada / Diamantina / MG and 65 vissungos sings. This work marked place in Brazilian social thought, inserting the author among the modernists miners, in Brazilian Folkloric Movement and in the national intellectual milieu among the most important authors who thought the Brazil in the first decades of that century. The book O negro e o garimpo em in Minas Gerais is a work that got intense reception, national and international, both in the humanities and in musical and artistic milieu, making cultural categories present in his thinking reached resonance echoing through the decades to the present day, allowing the expression of this cultural miner panning participate in the Brazilian social and cultural history.